Switching Loss Reduction of Dual Inverters using Isolated Voltage Sources Fed an Open-End Winding Interior Permanent Magnet Synchronous Motor - Lee, Hyung Woo; Lee, Kyo Beum (Conference Proceedings - IEEE Applied Power Electronics Conference and Exposition - APEC, 2023)
This paper presents the voltage modulation method to reduce switching loss of dual inverters fed open-end wingding interior permanent magnet synchronous motor (OEW-IPMSM). the dual inverters motor drive system that employs an open-end winding motor is increasingly used because of its advantages, such as being able to boost a voltage and a multi-level effect caused by the structure of a topology. However, in a dual inverters system, essentially the system operates through two inverters, so an increase of switching loss acts as an inevitable disadvantage of the system. This paper proposes a voltage modulation technique for reducing the switching loss of dual inverter for driving OEW-IPMSM. The proposed voltage modulation method operates on the basis of level-shift and discontinuous pulse width modulation (DPWM) and significantly reduces switching loss compared to the conventional voltage modulation technique of the dual inverters. The validity of the proposed voltage modulation method of dual inverters is verified by the simulation results.
Keywords: Discontinuous pulse width modulation; Dual inverters; Interior permanent magnet synchronous motor; Loss reduction; Open-end winding motor; Open-end windings; Open-end wingding interior permanent magnet synchronoi motor; Pulsewidth modulations (PWM); Switching loss; Switching loss reduction; DPWM; dual inverters; OEW-IPMSM; open-end winding motor; switching loss reduction